2011
DOI: 10.1159/000327726
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Morphological Distribution of Metastatic Foci in Lymph Nodes with Gastric Cancer

Abstract: Background/Aims: The morphological distribution of tumor cells in metastatic lymph nodes has been investigated in positive sentinel lymph nodes in several solid cancers. The aim of this study was to clarify the effect of the distribution of metastatic foci in lymph nodes on the prognosis in gastric cancer. Methods: The distribution of metastatic foci in the 100 node-positive patients who had undergone curative gastrectomy were classified into two groups: (1) massive type, in which the tumor occupied the entire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Contrary to that, Fukagawa et al [22,43] detected no influence on survival in two different studies, neither for mi-positive nor for ITC-positive patients with pT2N0M0 gastric carcinoma and D2 dissection. Another approach to LN evaluation was made by Nakamura et al [44] who classified metastatic LN into a massive type with tumor occupation of the entire LN and a non-massive type with only partial LN infiltration; the 10-year-survival was significantly poorer in the massive type group. In the present study LN mi, which would clearly be regarded as the non-massive type, showed an Fig.…”
Section: Survival Analysismentioning
confidence: 99%
“…Contrary to that, Fukagawa et al [22,43] detected no influence on survival in two different studies, neither for mi-positive nor for ITC-positive patients with pT2N0M0 gastric carcinoma and D2 dissection. Another approach to LN evaluation was made by Nakamura et al [44] who classified metastatic LN into a massive type with tumor occupation of the entire LN and a non-massive type with only partial LN infiltration; the 10-year-survival was significantly poorer in the massive type group. In the present study LN mi, which would clearly be regarded as the non-massive type, showed an Fig.…”
Section: Survival Analysismentioning
confidence: 99%